2019
DOI: 10.1111/jasp.12586
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intergroup contact on solidarity‐based collective action is mediated by reductions in SDO

Abstract: This paper explores the impact of positive and negative intergroup contact on advantaged group members’ willingness to engage in collective action on behalf of disadvantaged outgroups, and the mediational role of social dominance orientation (SDO) in this process. SDO captures an individual’s ideological support for inequality. If contact is going to promote collective action to reduce inequality among the advantaged group, it must be expected to influence their ideological beliefs about hierarchy. In Study 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Although prior research has shown that SDO (Meleady & Vermue, 2018) and system justification (Osborne et al, 2019) are associated with resisting BLM, we uniquely examined (a) the process by which ideologies and racial system justification contribute to prejudicial outcomes and (b) the prominence of social Darwinism as an ideological basis for defending the racial status quo in Study 2. Having supported our hypotheses in the domains of racial and gender prejudice, we next turned our attention to classism (i.e., prejudice against or in favor of people belonging to a particular social class).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although prior research has shown that SDO (Meleady & Vermue, 2018) and system justification (Osborne et al, 2019) are associated with resisting BLM, we uniquely examined (a) the process by which ideologies and racial system justification contribute to prejudicial outcomes and (b) the prominence of social Darwinism as an ideological basis for defending the racial status quo in Study 2. Having supported our hypotheses in the domains of racial and gender prejudice, we next turned our attention to classism (i.e., prejudice against or in favor of people belonging to a particular social class).…”
Section: Resultsmentioning
confidence: 99%
“…Second, our findings may be circumscribed to the United States. Key tenets of system justification theory have been supported cross-culturally (for a review, see Jost, 2019), and both SDO and system justification were associated with resisting BLM movement in England (Meleady & Vermue, 2018) and in New Zealand (Osborne et al, 2019). Nonetheless, future research is necessary to generalize our findings to other cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contact also impacts outcomes via lowered SDO. Meleady and Vermue (2019) found that White participants' positive contact with Blacks, and British participants' positive contact with immigrants, predicted increased support for the Black Lives Matters movements and EU rights via lower SDO. Moreover, Meleady, Crisp, Dhont, Hopthrow, and Turner (2019) found, across several studies (one longitudinal), that positive contact predicted greater environmental concern and pro‐environmental behaviors via lower SDO.…”
Section: Contact Effects On Individual Differencesmentioning
confidence: 99%
“…Contact research has, however, shown that improving outgroup attitudes does not equate to fostering collective action (Saguy et al., 2017). The role of negative intergroup contact as an instigator of collective action is of particular interest and has recently started to be examined (Meleady & Vermue, 2019). In the present research, therefore, we focus on examining negative (media) vicarious contact, testing whether it can lead advantaged group members to actively support the disadvantaged group, using both correlational and experimental methodologies.…”
Section: Media Vicarious Contactmentioning
confidence: 99%